Macho Icons Going Places - Muhammad Asghar; Muhammad Arshad Rehmani (Journal of Visual Art and Design, 2019)
This paper is an exploration of the increasing trend of popular macho representations on the back of three-wheeled auto rickshaws in the Punjab, Pakistan. Through an ethnographic field research it was observed that the painted visuals of popular icons in clichÃ©d heroic poses are rampant on rickshaws, representing a mobile exhibition of urban folk art. These visuals are mostly taken from the local Punjabi film industry, which has eclipsed over the past two decades. This study further explored the reasons for the increase of male figures displayed on rickshaws (and other) popular art and the almost total extinction of female figures because of increased religious assertion in Pakistan over this two-decade period. Our analysis shows that the relationship between rickshaw drivers and a common male audience with these powerful visuals is so strong that it reinforces the 'impulse to image'. The power of macho visuals satisfies the taste of cinemagoers who love to travel by rickshaws loaded with such visuals. We argue that these macho ideal representations have a strong impact on the beholders and they influence society through the power they convey. Finally, this study concludes that the popular macho visuals effectively communicate real emotions and please the mood of vast audiences in particular segments of society.